Silicone impression material foreign body in the middle ear: Two case reports and literature review. Issue 5 (October 2015) - Suzuki, Nobuyoshi; Okamura, Koji; Yano, Takuya; Moteki, Hideaki; Kitoh, Ryosuke; Takumi, Yutaka; Usami, Shin-ichi
Abstract: We report two cases of impression material foreign body in the middle ear. The first case had been affected with chronic otitis media. The silicone flowed into the middle ear through a tympanic membrane perforation during the process of making an ear mold. About 4 years and 8 months after, the patient had severe vertigo and deafness. We found bone erosion of the prominence of the lateral semicircular canal and diagnosed labyrinthitis caused by silicone impression material. In the second case silicone flowed into the canal wall down mastoid cavity. Both cases required surgery to remove the foreign body. The clinical courses in such cases are variable and timing of surgery is sometimes difficult. In addition to reporting these two cases, we present here a review of the literature regarding impression material foreign bodies.